Study on Pattern Reconfiguration of Plasma Antenna Excited by Surface Wave - Zhu Anshi; Chen Zili; Wei Jianbin; Zhen Yunhui (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
For the purpose of anti-jamming communications, the radiation pattern reconfiguration of plasma antenna excited by surface wave were studied. The self-consistent model used to describe the relation between the pump signal and radiation pattern is put forward by combining the Boltzmann Equation and Maxwell Equation. And the correctness of the model is validated by using FDTD approach. The experiment system that used to measure the radiation pattern is established to validate the correctness of the self-consistent model. The investigation results show that the radiation pattern are reconfigurable by controlling the pump signal.